Tonsillar Lymphangiomatous Polyps: A Rare Case Report - Ahmadi, Aslan; Zobairy, Hosna; Sanaei, Ayda; Dadkhah , Soraya; Salem, Mohammad Mahdi; Davoodi, Farzin; Mosleh, Haideh; Naseri , Reza (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2023)
Background: Tonsillar Lymphangiomatous Polyp (TLP) is a rare hamartomatous lesion composed of lymphangiectasia fibro-lipomatous elements. Its stromal framework includes adipose tissue with dilated lymphatic ducts and lymphoid tissue. Despite its rarity, TLP can be challenging to classify due to its unique clinical and pathological characteristics. In this context, we present a comprehensive examination of a TLP patient and documented TLP cases. Case presentation: A 27-year-old man was referred to the Kurdistan Otolaryngology Clinic due to persistent snoring, difficulty swallowing, and a foreign body sensation in his throat. A pedunculated mass was found on the superior pole of the right tonsil. He underwent a bilateral tonsillectomy, and the pathological examination revealed lymphangiomatous polyps. The patient had no postoperative bleeding and showed no recurrence after a year. Discussion: The head and neck region is the most common area for lymphatic lesions, particularly lymphangiomas. While tonsillar lymphangiomatous tumors are rare, identifying them in this area can be challenging. Tonsillar lymphangiomatous polyps are benign tumors that can sometimes be misdiagnosed as malignant neoplasms. Common clinical presentations of lymphangiomatous polyps included dysphagia, dyspnea, and a sensation of having a foreign body in the throat. Surgical removal through tonsillectomy is the established treatment approach, with no documented instances of post-surgery recurrence. Conclusion: We studied a Tonsillar Lymphangiomatous Polyp (TLP) case and provided a comprehensive understanding of its clinical, histopathological, and immunohistochemical attributes. Accurate diagnosis requires histological evaluation, and the recommended treatment involves complete removal of the tonsils.